2015
DOI: 10.18632/oncotarget.5529
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating drivers of oral epithelial dysplasia formation and malignant transformation to cancer using RNAseq

Abstract: Oral squamous cell carcinoma (OSCC) is a prevalent cancer with poor prognosis. Most OSCC progresses via a non-malignant stage called dysplasia. Effective treatment of dysplasia prior to potential malignant transformation is an unmet clinical need. To identify markers of early disease, we performed RNA sequencing of 19 matched HPV negative patient trios: normal oral mucosa, dysplasia and associated OSCC. We performed differential gene expression, principal component and correlated gene network analysis using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…The accumulation of somatic mutations in genes and molecular pathways is a major factor in the development of OSCC. Whole transcriptome sequencing (RNA‐Seq) is a superior approach which enables detection of somatic mutations and gene expression of coding and noncoding RNA; simultaneously …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accumulation of somatic mutations in genes and molecular pathways is a major factor in the development of OSCC. Whole transcriptome sequencing (RNA‐Seq) is a superior approach which enables detection of somatic mutations and gene expression of coding and noncoding RNA; simultaneously …”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation may represent a potential common denominator in development of OSCC . Microarray analysis of gene expression in OSCC cell lines with high basal NF‐KB activity and patients with OSCC samples identified dysregulation of many genes involved in inflammation, wound healing, angiogenesis, and growth regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All bam files underwent base recalibration and indel realignment (GATK v3.4–46) . RNAseq data was processed as previously described …”
Section: Methodsmentioning
confidence: 99%
“…However, several studies showed a wide range (5%‐27%) of transformation risks, mainly depending on dysplasia grade . It is believed that during malignant transformation, the dysplastic cells may escape from destruction mediated by the adaptive immune system …”
Section: Introductionmentioning
confidence: 99%